PENINGKATAN KOMPETENSI DESAIN WEB BAGI SISWA SEKOLAH MENENGAH KEJURUAN (SMK) SECARA DARING - Irma Permata Sari; Hamidillah Ajie (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2021)
Online business has been raised rapidly in recent times. This is a challenge for a web developer or web designer. According to the Bureau of Labor Statistics, job opportunities as web development are projected to grow by 27% from 2014 to 2024. But web course material provided at Vocational high School is still limited to basic material. We know that Vocational High Schools are formed to prepare graduates who are ready to work and become a solution to unemployment problem. A programmed, it is called ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œPengabdian Pada MasyarakatÃƒÂ¢Ã¢â€šÂ¬Ã‚Â, gives a training to society, in our study case is Vocational high School Binakarya Mandiri 2 Bekasi. This training was held with online platform and attended by around 25 students. The results of this training are 1) e-commerce website products, 2) training modules, and 3) video tutorials. We can be concluded that this activity can support vocational students programming skills.